BANK SYARI'AH MENGHADAPI TANTANGAN DAN HARAPAN - MEIRISON MEIRISON (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. Islam has shown how to look for halal sustenance in the form of instructions that can be understood through the rules that are understood by the scholars in the running of the economy based al-Ghanam bi al-gharam (dare to take profits and bear the losses) that is based on justice. Financial institutions is an important sector in a country that manages foreign exchange and provides services in the areas of finance, such as loans, insurance, production in various forms. individual or group of people can not be separated from the corridor and road rules. Bank Islam is growing in the midst of a system that forced him to comes the question of Islamic banks could face challenges, whether Islamic banks could take advantage of the excess savings that come from Muslim and non-Muslim communities, what is the best way to be traversed by the Islamic bank in the future. This paper aims to explain the problems and challenges faced by Islamic banks Modern and instill hope and vision of the future for Islamic banks in the future we expect the Islamic banks can face the challenge that comes from all directions.Let the money market established a large money market which can accommodate investment of surplus in Islamic banks and issued securities as supporters. Murabaha trading away that there are elements of fraud.